Sentinel lymph nodes identification in vulvar cancer--methods and technique - Rob, L; Robová, H; Pluta, M; Strnad, P; Kacírek, J; Chmel, R; Teslík, L; Skapa, P; Táborská, K (Ceská gynekologie, 2006)
To evaluate detection of sentinel lymph nodes (SLN) in squamous vulvar cancer with blue dye and 99mTc. The study describes technique of application, timing, management, detection rate (DR), specific side detection rate (SSDR) and false negative rate. Prospective clinical study. Department of Obstetrics and Gynecology, Charles University Prague, 2nd Medical Faculty, Teaching Hospital Motol. 46 women with squamous cell carcinoma tumors stage I or II, <4 cm with no clinical suspect lymph nodes were included. Blue dye alone was used in 16 women and the combination of 99mTc and blue dye was used in 30 women. Radiocoloid 99mTc was applied 3-5 hours and blue dye 3-5 minutes prior to ingvinal incision. We detected 88 SLN in 61 inguinal spaces. The detection rate in the blue dye group was 68.8 % (11 cases). One false negative SLN (6.3 %) appeared in this group. In blue dye+ 99mTc group detection rate was 100 % with no false negative SLN. Detection of SLN in squamous vulvar cancer with the combination of 99mTc and blue dye was statistically significantly more effective than using the blue dye alone.